Implementation of a colorectal cancer screening intervention in Malaysia (CRC-SIM) in the context of a pandemic: study protocol. Issue 9 (1st September 2022) - Schliemann, Désirée; Ramanathan, Kogila; Ibrahim Tamin, Nor Saleha Binti; O'Neill, Ciaran; Cardwell, Christopher R; Ismail, Roshidi; Nanu, Prathibha; Mohd Ghazali, Ahmad Nizal bin; Kee, Frank; Su, Tin Tin; Donnelly, Michael
Abstract : Introduction: Colorectal cancer (CRC) is the second most common cancer in Malaysia and cases are often detected late. Improving screening uptake is key in down-staging cancer and improving patient outcomes. The aim of this study is to develop, implement and evaluate an intervention to improve CRC screening uptake in Malaysia in the context of the COVID-19 pandemic. The evaluation will include ascertaining the budgetary impact of implementing and delivering the intervention. Methods and analysis: The implementation research logic model guided the development of the study and implementation outcome measures were informed by the 'Reach, Effectiveness, Adoption, Implementation and Maintenance' (RE-AIM) framework. This CRC screening intervention for Malaysia uses home-testing and digital, small media, communication to improve CRC screening uptake. A sample of 780 people aged 50–75 years living in Segamat district, Malaysia, will be selected randomly from the South East Asia Community Observatory (SEACO) database. Participants will receive a screening pack as well as a WhatsApp video of a local doctor to undertake a stool test safely and to send a photo of the test result to a confidential mobile number. SEACO staff will inform participants of their result. Quantitative data about follow-up clinic attendance, subsequent hospital tests and outcomes will be collected. Logistic regression will be used to investigate variables that influence screening completion and we will conduct a budget impact-analysis of the intervention and its implementation. Qualitative data about intervention implementation from the perspective of participants and stakeholders will be analysed thematically. Ethics and dissemination: Ethics approval has been granted by Monash University Human Research Ethics Committee (MUHREC ID: 29107) and the Medical Review and Ethics Committee (Reference: 21-02045-O7G(2)). Results will be disseminated through publications, conferences and community engagement activities. Trial registration number: National Medical Research Register Malaysia: 21-02045-O7G(2).